Seismic Fragility Analysis of Base Isolated Structure Subjected to Near-fault Ground Motions - Liu, Chengqing; Fang, Dengjia; Yan, Zhengxi (Periodica Polytechnica Civil Engineering, 2021)
In order to better evaluate the performance of the base isolated structure under the near-fault earthquakes, this paper takes into consideration an existing engineering case study in China as the prototype, and uses OpenSEES platform to establish the nonlinear finite element model of the base isolated structure. The nonlinear response of the isolated structure under the near-fault earthquake is analyzed. The incremental dynamic analysis (IDA) method is used to calculate the damage probability of the structure under the near-fault earthquake, and the fragility curve of the base isolated structure is established. The fragility equation is obtained by nonlinear regression, and the error of fragility equation is analyzed. The results show that the maximum value of the inter-story drift of the upper structure under the action of near-fault earthquake is significantly greater than that under the action of far-fault earthquake. With the increase of seismic intensity, the damage probability of base isolated structure increases nonlinearly, and the maximum response value of horizontal displacement of bearing and inter-story drift of superstructure increases generally. In addition, the exceeding probability of the fragility curve based on PSDA is greater than that based on EDP criterion. When the sample points of the two methods are the same, the exceeding probability points calculated based on PSDA can be regarded as accurate values. The fragility curve based on PSDA may overestimate the exceeding probability to some extent, and the overestimation may be enlarged with the increase of failure stage.